2021
DOI: 10.1021/acs.jpcc.0c11241
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Perovskite Glass Material in Photocatalysis Field

Abstract: So far, the application of inorganic glass materials in the field of photocatalysis has not been explored. First, phase separation induced CsPbBr3 quantum dot glasses, as an unprecedented method, is proposed in this work. The results show that the fluorescence intensity of quantum dots (QDs) glass is increased by 1.5 times compared with the initial intensity after the thermal cycle, showing excellent thermal stabilities. Furthermore, the quantum dots glass material is used for the first time in antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Compared with the PG, the binding energy of Cs 3d of the CsPbBr 3 QDs@glass sample moves to the lower energy band in XPS, which also indicated that Cs ions are involved in the formation of CsPbBr 3 QD in the glass after heat treatment because the Br ions bonding with Cs ions present a much lower binding energy compared with that of Cs ions bonding with O ions. 15 The binding energy peak of Pb ions almost has no change, indicating that the crystallization environment of Pb ions does not vary after heat treatment. All these results in evidence confirm the existence of CsPbBr 3 QDs in the glass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the PG, the binding energy of Cs 3d of the CsPbBr 3 QDs@glass sample moves to the lower energy band in XPS, which also indicated that Cs ions are involved in the formation of CsPbBr 3 QD in the glass after heat treatment because the Br ions bonding with Cs ions present a much lower binding energy compared with that of Cs ions bonding with O ions. 15 The binding energy peak of Pb ions almost has no change, indicating that the crystallization environment of Pb ions does not vary after heat treatment. All these results in evidence confirm the existence of CsPbBr 3 QDs in the glass.…”
Section: Resultsmentioning
confidence: 99%
“…To date, CsPbBr 3 QDs have been precipitated in phosphate glasses, borosilicate glasses, borogermante glasses, and tellurite glasses through conventional melt-quenching and subsequent thermal treatment. In addition, the chemical composition, morphology, and PLQY of CsPbBr 3 QDs can be tuned by adjusting the chemical composition of the glass and heat-treatment conditions. However, the fact that the rigid and highly polymerized structure of the glass matrix limits the in situ growth of CsPbBr 3 QDs cannot be ignored; thus, almost all reported morphologies of CsPbBr 3 QDs in different glasses are nearly spherical.…”
Section: Introductionmentioning
confidence: 99%
“…However, the modulation bandwidth of this class of devices is significantly limited by the long response times of color-converting materials [38]. The traditional phosphor material used as the color conversion layer is yttrium aluminum garnet (YAG) phosphor Y 3 -xAl 5 O 12 :xCe 3+ (YAG:Ce) [39], which has a critical limitation for VLC applications due to the slow phosphor conversion process caused by the long excited-state lifetimes [40], on the order of microseconds. The modulation bandwidth of phosphors is typically only a few MHz [41].…”
Section: Vlc Applications With Qd-based Color-conversion μLedsmentioning
confidence: 99%
“…However, there are only a few studies on CsPbX 3 PeQDs encapsulated in the tellurite glass system, and only the synthesis of CsPbBr 3 PeQDs has been realized by heat treatment. [14][15][16] In the existing studies, the widest tunable spectral range of CsPbBr 3 PeQDs is limited from 469 nm to 520 nm in tellurite glass. 17 In addition, the spectra regulation of CsPbBr 3 PeQDs in tellurite glass can only be achieved by adjusting the temperature and time of heat treatment or doping impurity ions into CsPbBr 3 PeQDs.…”
Section: Introductionmentioning
confidence: 99%